2015
DOI: 10.1152/ajpheart.00445.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmission to parasympathetic cardiac vagal neurons in the brain stem is altered with left ventricular hypertrophy-induced heart failure

Abstract: Neurotransmission to parasympathetic cardiac vagal neurons in the brain stem is altered with left ventricular hypertrophy-induced heart failure. Am J Physiol Heart Circ Physiol 309: H1281-H1287, 2015. First published September 14, 2015; doi:10.1152/ajpheart.00445.2015.-Hypertension, cardiac hypertrophy, and heart failure (HF) are widespread and debilitating cardiovascular diseases that affect nearly 23 million people worldwide. A distinctive hallmark of these cardiovascular diseases is autonomic imbalance, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…These neurons express the milieu of channels that were observed by Goldberg and Gourine 15,16 and have the requisite Chat and Ache expression corresponding to cholinergic neurons. These neurons also highly express the more standard GABAA and GABAB receptor subunits, in line with observations that a subset of DMV motor neurons were especially sensitive to GABAergic signaling 17 . It is notable that neuronal state E constitutes a greater proportion of samples than any other of the distinguishable states.…”
Section: Characterization Of Homeostatic Molecular States Of Dmv Neuronssupporting
confidence: 85%
“…These neurons express the milieu of channels that were observed by Goldberg and Gourine 15,16 and have the requisite Chat and Ache expression corresponding to cholinergic neurons. These neurons also highly express the more standard GABAA and GABAB receptor subunits, in line with observations that a subset of DMV motor neurons were especially sensitive to GABAergic signaling 17 . It is notable that neuronal state E constitutes a greater proportion of samples than any other of the distinguishable states.…”
Section: Characterization Of Homeostatic Molecular States Of Dmv Neuronssupporting
confidence: 85%
“…However, age-related reduction in the population of DVMN neurons in the SHRs might also be accompanied with abnormalities in DVMN neuronal excitability. Previous studies have shown that parasympathetic neuronal dysfunction is a common feature in animal models of cardiovascular disease such as heart failure and chronic intermittent hypoxia in which increased GABAergic/glycinergic neurotransmission and decreased excitatory neurotransmission in the DVMN and nucleus ambiguous result in reduced neuronal excitability and lower parasympathetic tone (39,40). Similar mechanisms are likely to operate in the SHR and should be further investigated in future studies to help determine whether DVMN synaptic dysfunction, a selective loss of parasympathetic preganglionic neurons supplying the heart or a remodelling of their cardiac projections, might promote abnormal changes in left ventricular inotropy and/or loss of structural integrity in the aortic wall which might contribute to the development of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is not surprising that most of these studies are performed using in vitro preparations of intracardiac neurons, what imposes several limitations to the interpretation of the respective findings. At this level the patch clamp technique has been widely used to understand the plasticity and function of intracardiac neurons [79,85], since it is the gold standard technique to analyze the electrical properties and functional connectivity of neurons. In addition the patch clamp technique offers the advantage to study simultaneously the function, organization and network of the ICNS.…”
Section: How To Study Icns?mentioning
confidence: 99%